Pengaruh Self-Efficacy Dan Dukungan Institusional Terhadap Entrepreneurial Intention Yang Dimoderasi Oleh Motivasi Intrinsik - Larasati, Adelia; Prayekti, Prayekti; Subiyanto, Didik (Universitas Hamzanwadi, 2025)
This study aims to analyze the effect of self-efficacy and institutional support on entrepreneurial intention with intrinsic motivation as a moderating variable in undergraduate students of the Management Study Program, FE, UST. This study uses a quantitative method with purposive sampling technique and involves 112 respondents who have taken entrepreneurship courses or similar courses. Data were collected through offline questionnaires and analyzed using AMOS. The results showed that self-efficacy has a significant effect on entrepreneurial intention, while institutional support has no significant effect. Intrinsic motivation significantly moderates the effect of self-efficacy on entrepreneurial intention, but does not act as a moderator in the relationship between institutional support and entrepreneurial intention. The implications of this study emphasize the importance of strengthening self-efficacy and intrinsic motivation in increasing students' entrepreneurial intentions, as well as the need to develop more effective institutional programs to support entrepreneurship